Beyond the Face: Double-Sided Renaissance Portraits and the Craft of Thought - Wijnands, Clim (Oxford University Press, 2024)
This essay investigates how touching and handling Renaissance portraits could serve as a memory technique. It analyses three paintings that solicited physical interaction: Giovanni Bellini’s Portrait of Giovanni Andrea Probi (once the lid of a chest); and two double-sided panels, Previtali’s Portrait of a Man; and Boltraffio’s Portrait of Girolamo Casio. The notion that memory resided in a (physical or symbolic) place in the back of the head was widespread in sixteenth-century Italy, and the backsides of double-sided portraits can be identified with such memory spaces. By bringing the portraits into dialogue with sixteenth-century texts on memory and art theory, I argue that they reflect the idea that memory and painting were sister arts. Critically adding to Carruthers’s notion of the craft of thought, I interpret the beholder’s physical interaction with portraits as a technique for shaping thoughts, making associations and forging links between beholders and portraits through the moving body.
Keywords: Renaissance Art; body; memory; portrait; touch; Taverne; Visual Arts and Performing Arts